(untitled) (Comparatismi, 2022)
This paper explores how Indigenous storytellers use graphic narratives to re-imagine Natives’ relationships with Canada in the aftermath of the trauma caused by Residential Schools. The representation of this experience has become a central theme in Indigenous storytelling in Canada since the 1980s. By focusing on contemporary Indigenous comics, the paper outlines how these narratives recollect the experience of abused Indigenous children to condemn the racists and colonial ideals that allowed those sufferings. These comics show how traumatic experiences suffered by the ancestors can be inherited by subsequent generations. Through storytelling, the community is capable of recuperating missing pieces of culture and histories that had long gone lost from the repertoire of Indigenous stories. Finally, this traumatic experience also effects speculative fiction set in the future.